ECOBRICK : ALTERNATIF PEMANFAATAN BOTOL PLASTIK BEKAS DI DESA KAJARTENGGULI SIDOARJO - Inggit Marodiyah; Atikha Sidhi Cahyana (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
ABSTRACT Plastic bottle waste is a wasted material. Waste still has economic value if it is reused into a useful item. The residents of the Kajartengguli village in Sidoarjo numbered 2637 people, which was dominated by women with a total of 1366 people, still often dispose of garbage by burning it. Training activities on the use of used plastic bottles for PKK women with the ecobrick method can provide a double function, namely knowledge of the use of used plastic bottles while reducing the volume of waste. The training method for making ecobricks begins with socialization, questions and answers, demonstrations, practice and mentoring. The results obtained are an increase in public understanding about plastic waste, ecobrick products and mothers can practice directly making plastic waste into ecobrick products